Prevention of occupational risks in a construction site using BIM - Tender, M. (2022)
Changing the document commonly used to manage occupational risks in construction in Portugal, the Safety and Health Plan, to the Building Information Modelling (BIM) format will be inevitable, as is already happening with other specialty projects. The management of the construction site is a part of that plan and it is important to obtain good logistic and financial results. However, it is also important due to the risks it creates for workers and third parties. This paper shares the first approach, in Portugal, to using 3D, 4D and 5D BIM to the construction health and safety site management, using a case study, and validates the approach with a comprehensive survey. The conclusions are that this approach allows for a better perception of risks and preventive measures; the improvement of the training level implemented; a better logistic and financial management of the construction site; and, finally, a better integration of prevention in the work planning.